IMPROVING THE COORDINATION AND EFFECTIVENESS OF AN INTEGRATED APPROACH TO MANAGEMENT OF LAND AND OTHER NATURAL RESOURCES - Teliura, N. O. (Municipal economy of cities. Series: «Economy science», 2016)
The development of new, more effective methods of caring for soil conservation, pest control, management, conservation and improvement of soil fertility, reduce the anthropogenic impact on the soil and reduce its pesticides, agrochemicals, sulphates, heavy pollution of metals. The problems of the deterioration of water bodies, resulting in flushing pollutants into rivers, lakes and reservoirs. In reservoirs, lakes and rivers the small levels of pollution, especially nutrients that significantly accelerate the processes of water bloom is much higher than in large flowing streams. Because of the "blooming" of water, quality is deteriorating, which complicates the use of water bodies for drinking water and recreation. Water bloom, dense aquatic population of microscopic photosynthetic organisms produced by an abundance of nutrient salts in surface water, coupled with adequate sunlight for photosynthesis. The microorganisms or the toxic substances that they release may discolour the water, deplete its oxygen content, poison aquatic animals and waterfowl, and irritate the skin and respiratory tract of humans. The framework of research authors suggested new methods of management and other natural resources, a regional program to improve the state of natural resources. Key words: soil cover, management of projects and programs, management of natural resources, degradation, erosion